DAMPAK EKSTERNALITAS PABRIK PENGOLAHAN KELAPA SAWIT (PKS) PT. TAMORA AGRO LESTARI (TAL) TERHADAP SOSIAL EKONOMI MASYARAKAT DI DESA SEROSAH KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI - Mai Oni Sandra; Ermi Tety; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are for: 1) To discover and descibe the externalize effect to a social society condition who lives arround the palm oil factory of PT. Tamora Agro Lestari, 2) To discover and describe the externalize effect to economic society condition who lives arround the palm oil factory of  PT. Tamora Agro Lestari, 3) To description the social society condition before and after the palm oil factory build at Hulu Kuantan sub district. This research was doing to palm oil factory of PT. Tamora Agro Lestari at Serosah village Hulu Kuantan sub district Kuantan Singingi regency. Sample was done by cluster sampling. Way the analis that used to aim to a society growth format, employment, income and dependency ratio. Society growth format before and after PKS buid have been changes in 2,99 percen it’s means that by buiding PKS still give not a big effect to develop the population other wise the employment had and effect look by partisipation growth worker as 1,36 percen and jobless go down in -25,84 percen. The employeis income in a month growth in about 60,38 percen from Rp.1.446.600 become Rp.3.652.000. Per capita income in a month growth about 54,51 percen from Rp.859.500 become Rp.1.889,833, the avverage income in a month honorer growth about 6,79 percen from Rp.1.767.278 become Rp.1.896.028and per capita income in a month growth about 8,72 percen from Rp.502.947 become Rp.551.037. Dependency ratio is about 53 percen it’s means at every 100 soul of produktif society was a dependency about 53 non produktif age. Society the changes of social society arround PKS is the changes fisicly (environmen and influence by new commer society or PKS employer).   Keywords: The Externalitation Effect, Social, Economic, Palm Oil Factory